Pain monitoring and medication assessment in elderly nursing home residents with dementia - Mette Marie Tang; Morten Gill Wollsen; Lise Aagaard (Journal of Research in Pharmacy Practice, 2016)
Objective: To monitor pain intensity, pain symptoms, and medication use in elderly with dementia. Methods: Nursing home residents above 65 years of age, diagnosed with dementia, and showing pain symptoms were included in the study. The patients′ mental status was monitored through a mini-mental state examination score and observations of pain symptoms using Part 1 of the Mobilization-Observation-Behaviour-Intensity-Dementia-2 (MOBID-2) pain scale. Community pharmacists reviewed the patients′ medication use, and the prescriptions were compared with guidelines for treatment of geriatric patients. Alterations to the patients′ medicine use were forwarded to the general practitioners. Findings: Sixty-one nursing home residents diagnosed with dementia were identified, 15 of these fulfilled the inclusion criteria, and 12 agreed to participate in the study. The mean age was 87 years of age (range: 77-96), and 42% of the residents were males. The patients′ overall pain intensity was 83% for observations on the numeric pain rating scale (NRS) >0 and 67% for NRS ≥3. Most painful were the situations in which the residents were to mobilize their legs, turn around to both sides of the bed, and when sitting on the bed. The medication reviews identified a total of 95 individual prescriptions, and 33% of these were for nervous system medications, followed by medicines for the treatment of alimentary tract and metabolism disorders (31% of total). Eleven prescriptions for pain medicine were identified; the majority of these were for paracetamol and opioids. Seventeen proposals to patients′ medication use were suggested, but the general practitioners accepted only 6% of these. Conclusion: This study indicates that the MOBID-2 pain scale in combination with medication reviews can be used as a tool for optimization of patients′ medication use. However, we recommend the conduction of a larger-scale study in multiple settings, to validate our results and the generalizability of the findings.